Stomatal Response of Carex Aquatilis to Climate Conditions in a Subarctic Coastal Wetland During the Growing Season - Kadonaga, Lisa Kaede (1989)
Plants can control water loss through their stomata in response to changing environmental conditions. Some research has been done on predicting stomatal resistance from climate variables such as solar radiation intensity, temperature, and vapour pressure deficit, but the factors involved are numerous and complex. Information on evapotranspiration from non-cultivated vegetation under field conditions is relatively scarce. This study was carried out in a subarctic coastal wetland on James Bay, an area for which little data exists. Leaf resistance measurements were collected in the field with a diffusion porometer as the 1988 growing season reached its peak. Meteorological data were also recorded. The main species examined was Carex aquatilis, a common sedge with a circumpolar distribution. As has been previously found, field resistances were lower than those reported for greenhouse-grown specimens. Attempts to derive a multivariate regression model to predict leaf resistances had a maximum explained variance under 40%. However, Principal Components Analysis suggested that cool, sunny, low-VPD conditions tend to accompany low leaf resistances. An increase in leaf resistance occurs when solar radiation intensities are low, or when the air is warm and dry. In addition, Carex aquatilis from drier areas showed less growth, and generally higher leaf resistances, than plants growing in saturated soils. Since climate models predict higher temperatures and lower soil moisture for the study area, due to carbon dioxide-induced warming, higher stomatal resistances could result. If these changes are severe enough, primary production could be reduced in the subarctic wetlands. Through the food chain, this could possibly affect species important to the economy and ecology of northern areas. Thesis Candidate in Philosophy